Impact of elderly gastrointestinal alterations on gastric emptying and enzymatic hydrolysis of skim milk: An in vitro study using a dynamic stomach system. (15th February 2023) - Zhang, Ping; Iqbal, Shahid; Deng, Renpan; Duan, Xu; Han, Huaxin; Dong Chen, Xiao; Wu, Peng
Highlights: In vitro digestion of skim milk was evaluated in the dynamic elderly and adult models. More clusters and protein aggregates shown under elderly digestion between 60 and 120 min. The gastric emptying half-time was 22.5 and 26.5 min for the young adult and elderly, respectively. Lower hydrolysis degree under elderly conditions (37.2%) compared to in the adult model (42.3%) Delayed gastric emptying and impaired proteolysis due to elderly gastrointestinal alterations. Abstract: This study aimed to evaluate gastric emptying and enzymatic hydrolysis of skim milk using a dynamic in vitro gastrointestinal system mimicking digestive conditions in young adult and elderly individuals. The gastric emptying half-time was 22.5 and 26.5 min in the young adult and elderly models, respectively. The degree of proteolysis at 120 min reached 42.3 % under adult digestion, significantly higher than that for the elderly (37.2 %). Moreover, milk proteins, particularly β-lactoglobulin, was more resistant to hydrolysis throughout elderly digestion. The slowed gastric emptying and impaired proteolysis were supported by the formation of more large clusters and protein aggregates under elderly digestion particularly between 60 and 120 min. This was attributed to the decreased gastric contractions and lowered digestive secretions in the elderly model that would impede the flow and breakdown of protein aggregates. This study is meaningful for future development of milk products that are more suitable for the elderly.